2014
DOI: 10.1002/2013gb004770
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐annual variability of organic carbon concentrations in running waters: Drivers along a climatic gradient

Abstract: Trends in surface water dissolved organic carbon (DOC) concentrations have received considerable scientific interest during recent decades. However, intra-annual DOC variability is often orders of magnitude larger than long-term trends. Unraveling the controls on intra-annual DOC dynamics holds the key to a better understanding of long-term changes and their ecological significance. We quantified and characterized intra-annual DOC variability and compared it with long-term DOC trends in 136 streams and rivers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 62 publications
(115 reference statements)
7
64
0
Order By: Relevance
“…In these areas, it is therefore important to have temporal sampling following decreases in concentrations and to relate them to lake concentrations during sampling. Lake inter-annual DOC and CDOM changes were 310 generally low in our study with an annual CDOM absorbance at A CDOM (340) = 0.41 cm -1 ± SD 0.05, corresponding to what is observed in larger water bodies where WRT integrates inflowing DOC and CDOM (Winterdahl et al, 2014). Inter-annual DOC and CDOM variations in groundwater from the lake catchment (Fig.…”
Section: Tracer Influences 300supporting
confidence: 60%
See 1 more Smart Citation
“…In these areas, it is therefore important to have temporal sampling following decreases in concentrations and to relate them to lake concentrations during sampling. Lake inter-annual DOC and CDOM changes were 310 generally low in our study with an annual CDOM absorbance at A CDOM (340) = 0.41 cm -1 ± SD 0.05, corresponding to what is observed in larger water bodies where WRT integrates inflowing DOC and CDOM (Winterdahl et al, 2014). Inter-annual DOC and CDOM variations in groundwater from the lake catchment (Fig.…”
Section: Tracer Influences 300supporting
confidence: 60%
“…S1) showed the same tendency as described for nutrients suggesting that sampling should be done at multiple times or in a period without drought or high rainfall. On a broader scale, the variation in DOC is known to be related to hydrology (Erlandsson et al, 2008), mean air temperature 315 (Winterdahl et al, 2014) and the recovery from acid deposition (Evans et al, 2006;Monteith et al, 2007). Sampling from wet areas with standing surface water resulted in high concentrations of most tracers (Table S1).…”
Section: Tracer Influences 300mentioning
confidence: 99%
“…A positive discharge‐DOC concentration relationship has commonly been observed for various catchments across boreal and temperate regions [ Hinton et al ., ; Raymond and Saiers , ; Laudon et al ., ]. But a strong temperature control on stream DOC concentration has previously only been suggested for catchments with a homogenous soil DOC profile typically found in peatland dominated areas [ Winterdahl et al ., ]. This study showed, however, that a strong temperature control could also be found for a hemiboreal catchment draining mineral soils.…”
Section: Discussionmentioning
confidence: 99%
“…On the spatial scale, DOC has been found to be mainly influenced by land-cover, in particular the percentage of wetland and open water in the catchment and the type of vegetation (e.g., Canham et al 2004;Kortelainen 1993;Larsen et al 2011;Sobek et al 2007;Xenopoulos et al 2003). On the temporal scale, DOC variation has been attributed to variation in hydrology (Erlandsson et al 2008), air temperature (Winterdahl et al 2014) and the recovery from acid deposition (Evans et al 2006;Monteith et al 2007). From the numerous DOC studies it becomes clear that main drivers of DOC, and thereby most likely also of a 420 , are not necessarily coherent between the spatial and temporal scale.…”
Section: Introductionmentioning
confidence: 99%